Comparison of Combined and Conventional Rehabilitation with Virtual Monitoring Method on Impulsivity in Parkinson's Patients - Rahbar, solmaz; Rostaee, Mohsen; Okhovatian, Farshad; Naimi, Sedigeh Sadat (Journal of Clinical Physiotherapy Research, 2021)
Introduction: Parkinson's disease is a chronic multisystem disease that can cause motor and non-motor symptoms and cognitive changes. One of the most important conservative treatments for Parkinson's disease is physiotherapy. Lack of simultaneous attention to the cognitive aspect of rehabilitation consistent with its physical aspect may be one of the effective reasons for the ineffectiveness of Parkinson's exercise therapy, which has not been considered before. Therefore, the purpose of this study was to compare the effect of fifteen sessions of combined rehabilitation (cognitive and exercise therapy) and conventional rehabilitation (exercise therapy) with virtual monitoring method on the impulsivity of Parkinson's patients. Materials and Methods: This pretest-posttest study had two groups of intervention. The patients were of both sexes and between 50 and 75 years old. The two groups of combined rehabilitation (n=32) and conventional rehabilitation (n=31) were examined for 15 sessions. Before and after the interventions, the level of impulsivity was determined by Barratt questionnaire. The method of measuring and monitoring the interventions in virtual space was designed and implemented. The scores obtained from the questionnaire were analyzed using SPSS 26 software. Mann-Whitney test was used to analyze the mean scores due to the abnormality of the variables. Results: The results showed that after 15 sessions of intervention, there was a significant difference between the two groups of samples in the impulsivity scores of unplanning and coping stability. Combined rehabilitation intervention (cognitive and exercise therapy) had a greater effect on patients' impulsivity than conventional rehabilitation (exercise therapy). Conclusion: Performing both combined and conventional rehabilitation interventions reduced the impulsivity of Parkinson's patients. However, in the group that received combined rehabilitation, the rate of this reduction was significant in most cases. Further interdisciplinary research between physiotherapy and cognitive rehabilitation is recommended, especially for neurological patients such as Parkinson's disease.